Schwannian stroma poor calcified bilateral neuroblastoma of adrenal gland: a rare case report - Desai, Killol N.; Savaliya, Sapana; Shah, Menka; Chaudhari, Sanjay (International Journal of Research in Medical Sciences, 2017)
Schwannian stroma poor calcified bilateral neuroblastoma of adrenal gland in 14 year old male patient is an exceptionally uncommon, malignant tumor that is derived from the primitive neural crest cells of the adrenal medulla. Neuroblastoma is the fourth most common malignancy of childhood up to five years of age, and very occasionally seen after that. It rarely occurs in the adrenal gland after ten years of age and bilaterally. The diagnosis was established based on clinical, radiological, histopathological and immunohistochemical features. At present, the patient is on chemotherapy and radiotherapy but the recent MRI is showing bilateral pubic bone and femur metastasis. Conclusion: Schwannian stroma poor calcified bilateral neuroblastoma of adrenal gland is a rare tumor at the age of 14 years which needs precise histopathological assessment and confirmation by Immunohistochemistry.